UPAYA PENCEGAHAN DAN SOLUSI TERHADAP TIMBULNYA PENCEMARAN LINGKUNGAN HIDUP DARI BUANGAN LIMBAH INDUSTRI - Siska Ratna Anjarsari; Rochmani Rochmani (Fakultas Hukum Universitas Stikubank, 2020)
Environmental pollution due to industrial waste disposal is a never-ending concern. There are more and more cases of environmental pollution due to industrial waste disposal, this is very disturbing and disturbing people's lives and threatens the preservation of environmental functions. The research method used in this research is juridical normative by tracing the rules and literature related to the problem under study. The aim of the research is to explain the prevention and solutions to pollution. The results showed that prevention efforts and solutions to the emergence of environmental pollution by planning a good, accurate and accurate production process reduce the use of auxiliary chemicals that are low in pollution load, control water use that is efficient and efficient, reuse and reuse. chemicals contained in liquid waste for production purposes as well as trying to monitor the waste resulting from post-waste minimization activities. Keywords : waste, environment, pollution, prevention, solutions.